Pengujian Beta Konsumsi dan Implikasinya Terhadap Imbal Hasil Saham Syariah di Indonesia dengan Mempertimbangkan Variabel Makro Ekonomi - Anita Anita; Ratu Humaemah; Asep Dadan Suganda (Faculty of Economic and Business, 2020)
This study aims to determine the effect of consumption beta on Islamic stock returns. The research model used Breeden's (1979) CCAPM model by adding macroeconomic variables as control variables in the first regression test. The sample selection used a purposive sampling technique and obtained 27 active Islamic stocks listed on the JII index during 2019. The data and information collected are historical data, namely the monthly closing price of the JII Islamic stock index, Gross Domestic Product Data, Inflation data and SBI interest rates. . The use of macroeconomic variable data is an effort to obtain a Goodness of fit model so that it is able to produce estimates in accordance with the actual value. The beta coefficient value obtained in the first test then carried out the second stage regression. The results prove that there is a negative influence between consumption beta on the average yield of Islamic JII stocks of 21.56%, with a consumption variable value of -0.046894 and a significant T value of 0.0147 <0.05. Thus, this research briefly proves that the CCAPM Breeden model (1979) applies to the JII Islamic stock index on the Indonesia Stock Exchange for the period 2019.